The Elephant in the Room: It is time to get the POSIX elephant off our necks. - Neville-Neil, George V. (Communications of the ACM, 2023)
The article provides an answer to a question concerning the reason for such large amounts of Python and C/C++ code present in programs, with a description of portable operating system interface standards (POSIX).